Analysis of Multiple PCR Bands in Drimia Species Obtained by R-Gene Specific Degenerate Primers: Life Sciences-Botany - Hanumantha Rao , H. M.; Rajanna, L. (International Journal of Life Science and Pharma Research, 2023)
Many studies confirmed that degenerate primers LM638 and LM637 amplify NBS-LRR Type R gene encoding sequences in both monocots and dicots. In addition, these primers also amplify nonspecific multiple bands along with specific amplification. The current study aims to explore the structure, role and reason for nonspecific bands in the amplification. The genomic DNA-degenerate PCR method was used to isolate the NBS-LRR type R-genes in Drimia species (synonym Urginea). Agarose gel electrophoresis was carried out for separation and visualization of amplified bands. The kit-based gel extraction method was followed to purify the PCR bands. Purified PCR bands were subjected to TA cloning. The plasmids which contain desired PCR bands were sequenced using the Sanger sequencing method. Multiple sequence alignment tool CLUSTALW was used to align sequences and MISA-Web tool was used to identify simple sequence repeats (SSR). The results of the study revealed that multiple sequence analysis of PCR bands of 600bp/500bp showed random deletions, presence of indels and frameshift mutations in the alignment. The sequence alignment also showed monomorphic sites between two sequences. Both 600 and 500bp were devoid of simple sequence repeats and the ORF finder confirmed the presence of irregular stop codons in the 600 bp sequences. The multiple sequence alignment tool was used in disclosing the structure and ancestor relationship between aligned Drimia sequences. The current study would help to explore pseudo genes in the genome of Drimia and to differentiate the orthologous and paralogous relationships in the sequences.